Surgical challenges of excision of retroperitoneal germ cell tumors in children: a single institutional study with literature review - Juliette F. Bollemeijer (Annals of Pediatric Surgery, 2021)
Abstract Background Retroperitoneal germ cell tumors (GCTs) are rare, commonly large tumors, often diagnosed in infancy. Complete surgical resection may pose a serious challenge as encasement of major vessels and organ displacement can lead to perioperative complications. This study aims to illustrate the surgical challenges of excising retroperitoneal GCTs. Results Nine patients were included: six patients with a teratoma, two patients with a mixed GCT with a yolk sac tumor component, and one patient with a pure yolk sac tumor. Six were males and seven were younger than 1 year of age at time of presentation. In all cases, perioperative vascular or organ-related complications occurred in one patient; this resulted in short bowel syndrome. There was no recurrence or mortality during the follow-up period. Relevant literature is reviewed and described. Conclusions The anatomical relation of a retroperitoneal GCT to the major vessels and organs is unpredictable. Preoperative radiological evaluation can help to improve the understanding of the vascular anatomy and to plan accordingly. Anteriorly displaced veins may appear insignificant and arteries, such as the superior mesenteric artery may be encased. Preoperative imaging may prevent perioperative complications, leading to safer surgical procedures. Level IV evidence Therapeutic study